Análise dos padrões de atividade do graxaim-do-mato (Cerdocyon thous) (Carnivora : canidae) no limite sul da Mata Atlântica - Santana, Arthur Venâncio de (2021)
The crab-eating fox (Cerdocyon thous) is a widespread Neotropical carnivoran that is locally abundant in many areas and occupies a variety of habitats, but that still presents important knowledge gaps regarding its ecology and behavior. This includes uncertainties with respect to the factors that drive its circadian and circannual activity patterns, as well as its interspecific interactions and how they vary over time. In this context, the present study aimed to characterize its circadian and circannual activity patterns at an Atlantic Forest field site, correlating it with abiotic variables and activity patterns of other sympatric mammals. To accomplish that, we deployed eight camera traps at RPPN Pró-Mata, southernmost Brazil, between July 2019 and July 2020. We obtained 657 records of 21 mammalian species and one group of species (small rodents); the most frequent of all (with 46% of the records) was C. thous. These records were compared to those from five other species/groups and assessed with respect to activity frequency relative to the lunar cycle. The results indicate that this canid presents a preferentially nocturnal activity pattern, with peaks of activity that vary relative to other geographic regions. When compared to other mammals, C. thous appears to avoid encounters with larger species, such as pumas (P. concolor) by using different times or avoiding their preferred locations. Our results were compared to previously reported data for other areas by performing an intensive bibliographic survey, which revealed 25 publications addressing this species’ activity pattern. This comparison indicated that abiotic variables play a minor role in driving this canid’s activity pattern, which seems to be influenced more strongly by biotic factors such as food availability and the presence of potential predators and competitors.